Lewis Eaton correspondence and newspaper - Eaton, Lewis, 1789-
ALsS from Eaton to George William Featherstonhaugh. ALS (Washington City; 1825 February 8) describing the excitement in Washington, D.C., preceding the presidential election. ALS (Washington City; 1825 February 9) announcing the election of John Quincy Adams, autographed by Walter F. Mondale. Includes the Columbian Centinel (Boston, Mass.; 1824 December 8) reporting the minutes of the electoral colleges.
U.S. representative from New York (State).
Collection material in English.
Keywords: Adams, John Quincy, -- 1767-1848.; Featherstonhaugh, George William, -- 1780-1866 -- Correspondence; Mondale, Walter F., -- 1928- -- Autographs; Columbian centinel (Boston, Mass. : 1804); American newspapers -- Massachusetts -- Boston; Electoral college -- United States; Presidents -- United States -- Election -- 1824.; United States -- Politics and government -- 1825-1829.; Washington (D.C.) -- History; Representatives, U.S. Congress -- New York (State)